(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
One of the world’s emerging nations, India boasts the second-largest arable landmass. A large portion of India’s population relies on agriculture for their livelihood. When compared to men, women in nations like India confront more restrictions and have a weaker economic & social standing. They have a hard time moving. Working on fields is just one of many responsibilities that rural women shoulder, along with tending to the home, cooking, and watering the crops. Their lives are certainly not easy. However, national accounts do not consider the many tasks done by rural women to be "economically active employment," even though they are crucial to the prosperity of rural households. In India, women represent 24 percent of the workforce in the agricultural sector and 41.1% of the workforce overall.